2010
DOI: 10.1111/j.1600-6143.2010.03132.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Organ Transplantation from Donors Poisoned with a Carbamate Insecticide

Abstract: Currently, liver transplantation is the only option for patients with end-stage liver disease. In Brazil, the mortality rate on the waiting list is about 25%. Multiple strategies to expand the donor pool are being pursed, however, grafts from poisoned donors are rarely used. This report documents successful liver, kidney and heart transplantations from four female donors who suffered brain death by hypoxia despite cardiopulmonary resuscitation following Aldicarb exposure ([2-methyl-2-(methylthio)propionaldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…[ 11 ] Studies have shown that victims of organophosphorus and carbamates poisoning have been overlooked as organs donors; these victims can turn out to be successful organ donors. [ 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Studies have shown that victims of organophosphorus and carbamates poisoning have been overlooked as organs donors; these victims can turn out to be successful organ donors. [ 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding organ donation after pesticide poisoning are scant [3,4]. Successful liver, kidney, and even heart donation has been reported after carbamate poisoning [3,4]. Carbamate compounds are reversible cholinesterase inhibitors undergoing rapid urinary excretion.…”
mentioning
confidence: 99%